Pendampingan dan Pelatihan Penyusunan AKM Bagi Guru di MTs Muhammadiyah 1 Malang - Effendi, Moh. Mahfud; Taufik, Marhan; Susanti, Reni Dwi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: Schools have yet to fully know and understand policies related to the Minimum Competency Assessment (AKM). Problems that are very important to overcome are related to the socialization and preparation of the AKM in schools. MTs Muhammadiyah 1 Malang, through Focussed Group Discussion (FGD) with the UMM service team, said that schools needed socialization and assistance in preparing AKM by teachers. Method: The solution offered is to provide socialization and help until the AKM is compiled to be implemented in schools. The implementation of this activity begins with socialization by education evaluation experts, and then assistance in the preparation of the AKM is carried out. Next, the teacher listened to the presentation of the AKM material by the speakers invited by the team. The team at the school carried out the following mentoring activity with the teacher. This is done to measure the increase in teachers' understanding of AKM from the overall activities carried out. Result: From the service activities' results, the training and mentoring implementation went smoothly and well. Participants responded to the service activities with high enthusiasm. Conclusions: This is evidenced by 52% of service participants being satisfied with the provision of AKM training, 62% being delighted with the provision of assistance in the preparation of AKM, and 48% being pleased with the assignments and evaluations provided by the service team.